Regional Labor Market: Forecasting the Economic Effect of Cooperation between Universities and Entrepreneurs - SHARAFANOVA, Elena Evgenyevna; FEDOSENKO, Yelena Anatol'yevna; SKHVEDIANI, Angi Erastievich (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The concept of public-private partnership (PPP) in higher education is clarified in the article as a mechanism for the formation of the human capital added value. PPP is considered as a set of organizational forms of long-term economic relations between state and non-state educational institutions, founders, private businesses and consumers of educational services for joint disposal of capital, as well as possession, appropriation, disposal, use of added value mediated by the influence of the regional labor market. The article shows that sustainable partnership is possible if and only if the interests of partners in the partnership subject matter coincide at a certain time interval, while the interest of entrepreneurs as PPP participants is most unstable in time, and the identified instability determines the main contradiction in the PPP development in higher education. This contradiction lies in the inconsistency of the timing of displaying the interests by educational institutions and regional government bodies, on the one hand, and business structures, on the other hand, within the process of implementing partner relations. The preparation of the master's degree holders as an educational service provided by an educational institution on a reimbursable basis is interpreted as rendering labor-intensive services with high market value. The analysis of the costs of PPP participants uses learning curves – the main component of a kind of strategic treadmill. Based on the use of learning curves, a scenario forecast of the economic effect obtained by educational institutions and partner organizations on the regional labor market was constructed with increasing cooperation scales. There was provided an algorithm for calculating the economic effect of cooperation between universities and entrepreneurs in the preparation of the master's degree holders.